Proportion of out-of-hospital adult non-traumatic cardiac or respiratory arrest among calls for seizure. Issue 9 (22nd November 2011) - Dami, Fabrice; Rossetti, Andrea O; Fuchs, Vincent; Yersin, Bertrand; Hugli, Olivier
Abstract : Objectives: To measure the proportion of adult non-traumatic cardiac or respiratory arrest among calls for seizure to an emergency medical dispatch centre and to record whether known epileptic patients present cardiac or respiratory arrest together with seizure. Methods: This 2-year prospective observational investigation involved the collection of tape recordings of all incoming calls to the emergency medical dispatch centre, in which an out-of-hospital non-traumatic seizure was the chief complaint in patients >18 years, in addition to the paramedics' records of all patients who presented with respiratory or cardiac arrest. The authors also recorded whether the bystander spontaneously mentioned to the dispatcher that the victim was known to have epilepsy. Results: During the 24-month period, the call centre received 561 incoming calls for an out-of-hospital non-traumatic seizure in an adult. Twelve cases were classified as cardiac or respiratory arrest by paramedics. In one case, the caller spontaneously mentioned that the victim had a history of epilepsy. The proportion of cardiac or respiratory arrest among calls for seizure was 2.1%. Conclusion: Although these cases are rare, dispatchers should closely monitor seizure patients with the help of bystanders to exclude an out-of-hospital cardiac or respiratory arrest, in which case the dispatcher can offer telephone cardiopulmonary resuscitation advice until the paramedics arrive. Whenever the activity of the centre allows it and no new incoming call is on hold, this can be achieved by staying on the line with the caller or by calling back. A history of epilepsy should not modify the type of monitoring performed by the dispatcher as those patients may also have an arrest together with seizure.